Relationship between urbanisation and pollutant emissions in transboundary river basins under the strategy of the Belt and Road Initiative. (July 2018) - Yu, Sen; Lu, Hongwei
Abstract: Urbanisation has increased the discharge of pollutants, altered water flow regimes, and modified the morphology of transboundary river basins. All these actions have resulted in multiple pressures on aquatic ecosystems of transboundary river basins, undermining the healthy development of their aquatic ecosystems as well as impairing the sustainable economic and social development associated therewith. Quantifying the relationship between socio-economic factors, and water environment systems, and understanding the multiple pressures in their combined impact on environmental fairness of transboundary river basins is challenging, and it is crucial to the strategic planning of the Belt and Road strategy. Here, the Songhua River basin, which is the largest branch of the China-Russia boundary river is taken as the study area. The Environmental Kuznets Curve (EKC) model, which is coupled with the integrated model (pollutant emissions intensity, pollutant discharge efficiency, and pollutant emissions per capita), are used to reveal the spatio-temporal variations in regional pollutant emissions in the SRB. The results show that the features of the EKC are present in the pollutant emissions during economic development of the SRB. It also demonstrates that the turning point value of the EKC appeared when the GDP per capita is around ¥40, 000 (CNY) in the SRB, which means that the pollutant emissions show an increasing trend, when the GDP per capita is less than ¥40, 000. Our findings could contribute to a better understanding of the coupling relationship between pollutant emissions in transboundary river basins and urbanisation process in water stress to help address water allocation problems. Highlights: This study identifies spatial and temporal characteristics of urbanisation process. Coupling relationship between urbanisation and pollutant emissions is built. The quantitative response model in transboundary river basin is established. The largest branch of China-Russia boundary river is taken as the study area. Results provide support for water management of countries along the Belt and Road.